(untitled) (Research, Society and Development, 2021)
The practice of surfing has been highlighted all over the world. Its practitioners have increased considerably, making it the most practiced water sport today. Because it is a sport that requires great physical effort and sudden changes in posture, your athletes are always at great risk of developing injuries. Thus, the objective of this study was to list the injuries that most affect surfers, as well as the conduct of athletes to avoid such injuries and also to understand the importance of the physiotherapist in the prevention and treatment of sports injuries. The methodology used in this research was a literature review, where literary searches were carried out on this subject in electronic databases such as Google Scholar, Scientific Electronic Library Online (Scielo), PubMed, with the purpose of analyzing and synthesizing the information found. Through this study it was possible to verify the main characteristics of the injuries that affect surfing athletes. Therefore, understanding the sports gestures of this modality and the conducts to be taken in order to minimize the risk of injuries and aiming at the benefits that promote analgesia, improve flexibility, muscle strength, physical and cardiorespiratory fitness is of great value, realizing that planning an injury prevention program with surfing athletes can be considered an excellent method for to reduce the number of injuries.